A metaheuristic for a sustainable distribution process. (6th February 2023) - Tayachi, Dalila; Nyako, Sidonie Ienra; Tagina, Moncef
This paper deals with a bi-objective green vehicle routing problem, where conventional economic and environmental objectives are both considered. More precisely, our work minimises distance and fuel consumption in the capacitated vehicle routing problem (FCVRP). Firstly, we consider fuel consumption minimisation and we propose an iterated local search to solve it as it is an NP-complete problem. In the fuel consumption calculation function, distance, load, and speed are considered simultaneously. The proposed metaheuristic is tested on Solomon's instances for each single objective and the experimental results are compared with those in the literature. Secondly, the epsilon-constraint method is applied to solve the bi-objective FCVRP where the total travelled distance and the fuel consumption are both minimised. A real-world case in Cameroon is considered in order to bring help to the decision-maker.